The Influence of Service Quality and Product Quality on Consumer Satisfaction at Bandar Coil, Surabaya City - MAULANA, Maulana (International Journal of Environmental, Sustainability, and Social Science, 2025)
This research aims to further examine the "Influence of Service Quality and Product Quality on Consumer Satisfaction" at Bandar Coil in Surabaya. The main focus of this study is to understand the relationship between service quality, product quality, and the level of consumer satisfaction at Bandar Coil. The background of this research is driven by the importance of identifying the factors that influence customer satisfaction and how the roles of service quality and product quality contribute to enhancing that satisfaction. The purpose of this study is to analyze the partial effects of service quality and product quality on consumer satisfaction, as well as the simultaneous effects of both variables on consumer satisfaction. The methodology used is a quantitative approach with survey methods, distributing questionnaires to Bandar Coil customers. The population consists of all customers of Bandar Coil during the year 2025, with a sample of 90 respondents selected using the Slovin formula. Data analysis is conducted using multiple linear regression analysis. The results show that, partially, product quality does not have a significant effect on consumer satisfaction, while service quality has a positive and significant impact. In terms of the combined effect, both service quality and product quality jointly influence the level of consumer satisfaction. The conclusion of this study indicates that service quality is the main factor affecting consumer satisfaction. Product quality, although not significantly impactful on its own, still contributes overall to increasing customer satisfaction.